The Effectiveness of Paralanguage in English as Foreign Language Classes - Seran, Yanuarius; Luruk, Fransiska Densiana; Verdial, Jose Da Conceicao; Kok, Alfian Sandy William; Seran, Yohanes (Universitas Nurul Jadid, 2025)
This study was carried out to investigate the effectiveness of paralanguage in English as Foreign Language (EFL) class. Descriptive qualitative method was utilised in this study. Researchers took paralanguage as the object of this study. Random sampling was applied in taking the sample. Source of the data were taken from observation check list and interview. The data were analysed using paralanguage theory. The result revealed that teachers implemented paralanguage in class. (1) healthy synergy could be created between teachers and students; (2) the tone or pitch of the voice helps provide confirmation of an explanation; (3) variations in tone can make the class atmosphere not flat and monotonous; (4) variations in tone, optimal voice volume according to students' conditions in the classroom, and clear accents and articulations can help students follow the teacher's explanation and students can comprehend the explanation of the material effectively; and (5) teachers’ preparation in the classroom determines the continuity of optimal teaching and learning and teachers can avoid frequent use of fillers which will lead to monotonous classes. The implication of this study is due to the significant influence of paralanguage in teaching and learning process, teachers especially English teachers need to apply paralanguage in class. An effective instruction not only does focus on the transferring the materials, nevertheless the effort applied to lead students to e comprehensive understanding of the materials learned.